Proceedings of the 23rd ACM/IEEE International Conference on Model Driven Engineering Languages and Systems: Companion Proceedi 2020
DOI: 10.1145/3417990.3421263
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based compatibility analysis in automotive systems engineering

Abstract: Software is the new leading factor for innovation in the automotive industry. With the increase of software in road vehicles new business models, such as after-sale updates (i.e., Function-on-Demand) and Over-the-Air-Updates come into focus of manufacturers. When updating a road vehicle in the field, it is required to ensure functional safety. An update shall not influence existing functionality and break its safety. Hence, it must be compatible with the existing software. The compatibility of an update is ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…To address this issue, the authors [18] conducted an analysis that looked at the consequences of changing risk parameters, with the ultimate goal of displaying the events discovered. The significance of this study lies in the ability to retest after the update has been implemented without interfering with critical functions.…”
Section: Aspects Of Security Inside Modern Vehiclesmentioning
confidence: 99%
“…To address this issue, the authors [18] conducted an analysis that looked at the consequences of changing risk parameters, with the ultimate goal of displaying the events discovered. The significance of this study lies in the ability to retest after the update has been implemented without interfering with critical functions.…”
Section: Aspects Of Security Inside Modern Vehiclesmentioning
confidence: 99%
“…To address this issue, the authors of [16] conducted an analysis that looked at the consequences of changing risk parameters, with the ultimate goal of displaying the events discovered. The significance of this study lies in the ability to retest after the update has been implemented without interfering with critical functions.…”
Section: Aspects Of Security Inside Modern Vehiclesmentioning
confidence: 99%
“…This section discusses studies P72 [44], P580 [71], P588 [72], P589 [73], and [89], which were found to address the safety analysis category.…”
Section: Safety Analysismentioning
confidence: 99%
“…As demonstrated by the example, changes are propagated in one model for both variant management and safety engineering. Pett et al [89] apply a risk-based change-impact analysis to an automotive architecture, combining risk-based testing, product sampling, and configuration prioritizing. They use information of the changes applied in a software update to prioritize relevant system variants for checking compatibility of an update to existing variants in the field.…”
Section: Safety Analysismentioning
confidence: 99%